E-009 Treatment of ruptured cerebral aneurysms is increasingly occurring in high volume centers in the USA. (12th July 2011) - Leake, C; Brinjikji, W; Kallmes, D; Cloft, H
Abstract : Purpose: Although there is no formal system for regionalization of care for subarachnoid hemorrhage, evidence of better outcomes at higher volume centers might be expected to result in more of these patients being referred to high volume centers. The purpose of this study was to evaluate the US National Inpatient Sample (NIS) from 2001 to 2008 for trends in patient admissions for treatment of ruptured aneurysms at high and low volume centers. Methods: We evaluated the numbers of ruptured aneurysms treated with clipping and coiling annually at low (≤20 patients/year) and high volume (>20 patients/year) centers, and also counted the number of high and low volume centers for each treatment. Hospitalizations for clipping or coiling of ruptured aneurysms were identified by cross-matching International Classification of Disease Codes for diagnosis of ruptured aneurysm (430.0) with procedure codes for clipping (39.51) or coiling (39.52, 39.79, or 39.72) of cerebral aneurysms. Results: (Abstract E-009 figure 1 ) In 2001, 31% (435/1392) of patients clipped and 0% (0/122) of patients coiled were treated at high volume centers, whereas in 2008 these numbers increased to 62% (627/1016) of patients clipped and 68% (917/1351) of patients coiled, respectively. For clipping, the number of low volume centers significantly declined from 177 centers in 2001 to 85 centers in 2008, while the number of high volume centers has remained constant at 13 to 15. For coiling procedures, the number of low volume centers decreased from 62 centers in 2001 to 54 centers in 2008, while the number of high volume centers substantially increased from 0 centers in 2001 to 16 centers in 2005 and remained constant thereafter. Conclusion: Treatment of ruptured cerebral aneurysms is increasingly occurring in high volume centers in the USA. This is a favorable trend in that better outcomes are associated with care for these patients at a high volume center.